Síntese e caracterização de poliacrilamidas modificadas para utilização na indústria do petróleo - Maia, Ana Maria da Silva (2008)
Modified polyacrylamides with ≅ 0.2 mol % of N,N-dihexylacrylamide and hydrolysis degree from 0 to 25 % were synthesized by micellar copolymerization. The hydrophobic monomer was obtained by the reaction between acryloyl chloride and N,Ndihexylamine and characterized by infrared (IR) and proton nuclear magnetic resonance (1H NMR) spectroscopy. The polymer molecular structures were determined through 1H and 13C NMR spectroscopy and the polymers were studied in dilute and semi-dilute regimes by viscometry, rheometry, static light scattering and photon correlation spectroscopy, at the temperature range from 25 to 55 ºC. The data obtained by viscometry showed that the intrinsic viscosity from the hydrolyzed polymers is larger than the precursor polymers at the same ionic strength. The comparison between the charged polymers showed that the polymer with higher hydrolysis degree has a more compact structure in formation water (AFS). The increase of temperature led to an enhanced reduced viscosity to the polymers in Milli-Q water (AMQ), although, in brine, only the unhydrolyzed polymer had an increase in the reduced viscosity with the temperature, and the hydrolyzed derivatives had a decrease in the reduced viscosity. The static light scattering (SLS) analyses in salt solutions evidenced a decrease of weight-average molecular weight (⎯Mw) with the increase of the hydrolysis degree, due to the reduction of the thermodynamic interactions between polymer and solvent, which was evidenced by the decrease of the second virial coefficient (A2). The polymers showed more than one relaxation mode in solution, when analyzed by photon correlation spectroscopy, and these modes were attributed to isolated coils and aggregates of several sizes. The aggregation behavior depended strongly on the ionic strength, and also on the temperature, although in a lower extension. The polymers showed large aggregates in all studied conditions, however, their solutions did not displayed a good increase in water viscosity to be used in enhanced oil recovery (EOR) processes